Penyuluhan Manfaat Baca Shalawat Dapat Menurunkan Stres Lansia Di RW 02 Karangrejo Wonokromo Surabaya - Siti Maimunah; Iis Noventi; Nunik Purwanti; Rusdianinseh; Nety Mawarda Hatmanti (LPPI UMN AL WASHLIYAH, 2025)
Many elderly people experience stress because of the problems they face, family problems, especially children who lack attention, lack patience When taking care of them, there are even those who do not care about the absence of guidance in old age, causing them to have a minimal understanding in the field of religion in the community of RW 02 Karangrejo Wonokromo Surabaya there are some people who can recite and lack understanding about religion Method: lecture and question and answer methodto find out the level of knowledge of the respondent can be found by conducting a pre-test in the form of a questionnaire that will be filled out by the respondent to find out the level of knowledge of the respondent about the Stress experienced by the elderly. The pre test is carried out before counseling is given, to find out the increase in respondents' knowledge about the effect of reading prayer on the stress of the elderly can be found by comparing the results of the post test that have been filled in by the respondents after the counseling is carried out with the results of the pre test. The result was that there was an increase in public knowledge because the post test score was higher than the pre-test score